2014
DOI: 10.1371/journal.pone.0102280
|View full text |Cite
|
Sign up to set email alerts
|

Structural Integrity of the Antigen Is a Determinant for the Induction of T-Helper Type-1 Immunity in Mice by Gene Gun Vaccines against E.coli Beta-Galactosidase

Abstract: The type of immune response is critical for successful protection and typically determined by pathogen-associated danger molecules. In contrast, protein antigens are usually regarded as passive target structures. Here, we provide evidence that the structure of the antigen can profoundly influence the type of response that is elicited under else identical conditions. In mice, gene gun vaccines induce predominantly Th2-biased immune reactions against most antigens. One exception is E. coli beta-galactosidase (βG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…In mice, GG vaccines usually induce IgG1 as the predominant antibody isotype. In contrast to many other antigens, including OVA, βGal induces also other IgG subtypes [ 19 , 28 ]. Testing serum samples of the mice described in Fig 1 revealed that ablation of langerin + cells caused a dramatic reduction in IgG1 against βGal ( Fig 2A , left panel) and, to a lesser extent, also a decline in IgG2c antibodies ( Fig 2A , right panel).…”
Section: Resultsmentioning
confidence: 99%
“…In mice, GG vaccines usually induce IgG1 as the predominant antibody isotype. In contrast to many other antigens, including OVA, βGal induces also other IgG subtypes [ 19 , 28 ]. Testing serum samples of the mice described in Fig 1 revealed that ablation of langerin + cells caused a dramatic reduction in IgG1 against βGal ( Fig 2A , left panel) and, to a lesser extent, also a decline in IgG2c antibodies ( Fig 2A , right panel).…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, this approach is mainly described for biolistic-mediated gene vaccinations to induce antigen-specific immune tolerance. 21,28 In 2011, Xia and colleagues 20 evaluated the localization of the gold particles in the epidermis and upper dermis after gene gun treatment. 20 In our study, the desired accumulation of the gold beads containing the transgene for Col7a1 correction in the BMZ and upper dermis was achieved in wild-type mice using a pressure of 300-400 psi, proving an efficient application into the skin.…”
Section: Discussionmentioning
confidence: 99%
“…β-gal was produced in house as a highly purified recombinant protein according to protocols previously described in detail [27]. All H 2 O solutions were prepared using water with a resistivity of 18 M Ω cm (Millipore, Milli-Q).…”
Section: Methodsmentioning
confidence: 99%
“…Na 2 CO 3 (Sigma Aldrich, ACS reagent, ≥99.5%), Na 2 HPO 4 (Sigma Aldrich, ACS Reagent ≥99%), citric acid (Sigma Aldrich, ≥99.5%), o-Nitrophenyl-β-D-galactopyranoside (ONPG, Sigma Aldrich, >99% HPLC), MgCl 2 (Sigma Aldrich, ACS Reagent >99%) and D 2 O (Aldrich, 99 atom% D) were used as received. β-gal was produced in house as a highly purified recombinant protein according to protocols previously described in detail [ 27 ]. All H 2 O solutions were prepared using water with a resistivity of 18 M Ω cm (Millipore, Milli-Q).…”
Section: Methodsmentioning
confidence: 99%